The use of dance to improve the health and wellbeing of older adults: A global scoping review of research trials. - Martha Waugh; Gregory Youdan; Courtney Casale; Rachel Balaban; Emily S Cross; Dafna Merom (PLoS ONE)
Background Dance is a promising health resource for older adults, but empirical evidence remains inconsistent. The lack of synthesised evidence regarding program design, dose, and delivery limits understanding of factors influencing participation and health outcomes. This scoping review aimed to map the scope, range, and effectiveness of dance programs for older people, and identify gaps and opportunities for future research and practice. Methods Searches across five databases (September 2023) identified 148 studies evaluating 116 dance programs (≥4 weeks) for older adults (≥55 years, N = 8060), Dance interventions delivered to clinical groups were excluded. Intervention design and delivery were charted against the TIDieR reporting checklist. Program outcomes including adherence, safety, and positive tests were charted into established taxonomies. Results Demographic information, program details, and implementation were often insufficiently reported. Participant groups differed by age range, with underserved communities underrepresented. Programs varied extensively in key factors including dose, prospective 'active ingredients', delivery approach, facilitator expertise, and class size. While dance was physically safe, adherence rates in older adults are comparable to other community exercise programs. Less than 40% of health assessments showed positive change, with more consistent benefits to physical endurance, strength, and function, moderate impacts on psychosocial health, and limited benefits to cognitive and brain health, and falls and falls risk. Conclusion Dance is a meaningful, safe, adaptable, and low-cost health resource for older adults. Key opportunities for advancing research include improved access for underserved groups, program suitability assessments, strategies to support adherence and engagement including theory-informed approaches, and incorporation of participant and practitioner insights. Identification of key 'active ingredients' and dance program factors may improve understanding of causal pathways and mechanisms to optimise engagement and health impacts. Stronger reporting practices will facilitate comparisons across studies and more robust evidence synthesis. This review provides a critical knowledge foundation to guide future approaches in dance for health and offers reporting recommendations.